Populism and anti-liberal thought: Lega and M5S in the Italian context - Adinolfi, G. (Conhecer: Debate entre o Público e o Privado, 2020)
This article discusses how the populist challenge can affect, directly or indirectly, the way the representative and liberal democracy works. Outside Latin America, Italy is one of the most typical cases of the populist challenge to liberalism. Indeed, in the General Election of spring 2018, the majority in the parliament was conquered by 2 populist groups: a) the Lega (17.35%); and b) the 5-Star MoVement (MoVimento 5 Stelle [M5S]) (32.68%). The main assumption herein is that the populist ideology should be encompassed by the larger family of anti-liberal thought. At that level, the populist representation shares some common points with fascism. Although the idea of populist representation is quite different from that of fascism, both of them are based on anti-liberalism and they have an intrinsic tendency to plebiscitarianism. That is, their focus lies on 2 dimensions: a) the differences and continuities between the Lega and the M5S; and b) the role played by anti-liberal thought. The second dimension is related to the idea of representation and it is divided into 2 further layers: a) how the populists build their own audience; and b) the institutional reshuffle they propose to enforce the people’s will.